2011
DOI: 10.1016/j.juro.2011.03.132
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Symptoms of Bladder Pain Syndrome/Interstitial Cystitis Among Adult Females in the United States

Abstract: Purpose Bladder pain syndrome/interstitial cystitis is a poorly understood condition that can cause serious disability. We provide the first population based symptom prevalence estimate to our knowledge among United States adult females. Materials and Methods We developed and validated 2 case definitions to identify bladder pain syndrome/interstitial cystitis symptoms. Beginning in August 2007 we telephoned United States households, seeking adult women with bladder symptoms or a bladder pain syndrome/interst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
363
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 471 publications
(373 citation statements)
references
References 13 publications
5
363
1
4
Order By: Relevance
“…Although participants endorsed bladder symptoms consistent with an IC/BPS diagnosis, it is possible that some participants would not meet diagnostic criteria in a clinical evaluation. However, a recent paper by our group has shown that the RICE sample reports Correlations between the IC/BPS symptom summary score and IC/BPS-specific symptoms (3)(4)(5) are not reported because the correlations will necessarily be inflated, as the items comprise the summary score. ** p < 0.001. similar severity of IC/BPS symptoms as a clinical population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although participants endorsed bladder symptoms consistent with an IC/BPS diagnosis, it is possible that some participants would not meet diagnostic criteria in a clinical evaluation. However, a recent paper by our group has shown that the RICE sample reports Correlations between the IC/BPS symptom summary score and IC/BPS-specific symptoms (3)(4)(5) are not reported because the correlations will necessarily be inflated, as the items comprise the summary score. ** p < 0.001. similar severity of IC/BPS symptoms as a clinical population.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the RAND Interstitial Cystitis Epidemiology (RICE) Study (from which the current data are drawn), a nationally representative population survey, up to 6.5% of US women reported experiencing IC/BPS symptoms according to established case criteria, but less than 10% of these women had an IC/BPS diagnosis. 3 Adding to the diagnostic uncertainty is the considerable symptom overlap and comorbidity between IC/BPS and other chronic pain conditions, such as fi bromyalgia, chronic fatigue syndrome, and irritable bowel syndrome (IBS). negative influences on quality of life (QOL).…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
See 2 more Smart Citations
“…Some people experience worsened symptoms with certain foods, and in females, menstruation [1]. Approximately 3.3 to 7.9 million (2.7% to 6.53%) female adults over 18 years of age [2] and 2.1 to 4.6 million male adults (1.9% to 4.2%) between 39 and 74 years of age [3] experience IC/PBS symptoms in the US. Despite the prevalence, no app exists to manage IC/PBS symptoms.…”
mentioning
confidence: 99%